IDENTIFIKASI VIRUS PENYAKIT JEMBRANA PADA SAPI BALI MENGGUNAKAN PENANDA MOLEKULER GEN env SU - Indriawati Indriawati; Endang Tri Margawati; Muhammad Ridwan (BERITA BIOLOGI, 2013)
Up to present, detection of Jembrana disease virus has been identified through serological test. Advances in molecular biology has enabled to detect Jembrana disease virus earlier, quicker and more accurate by application of molecular markers.The aim of this study was to identify Jembrana disease by using molecular marker of env SU gene in Bali cattle.Total RNA of Jembrana disease virus (7732bp) was collected from spleen of Bali cattle suspected Jembrana disease by using RNEasy Protect Mini Kit (QIAGEN). A pair of specific primers was designed from Jembrana viral genome (env SU) that accessed through a GenBank with Accession Number of U21603.A kit of Access Quick RT-PCR System (PROMEGA) was used for Reverse-Transcriptase-PCR (RT-PCR). The RT-PCR products were visualized on 2% agarose gel.The result showed a single band with the size of ± 900bp in all samples. This size indicated that env SU gene was existed in the examined spleen samples. This finding suggests that a molecular marker could be used accurately to identify the env SU gene in JDV of Bali cattle.